Best Upper and Lower Tchebycheff Bounds on Expected Utility - Willassen, Yngve (Review of Economic Studies, 1990)
It is useful to have bounds on expected utility in situations in which the relevant distribution is skewed. This paper assumes that the third moment of the distribution is known and uses knowledge of the first three moments to derive upper and lower Tchebycheff bounds. Copyright 1990 by The Review of Economic Studies Limited.